PERAN DIREKTORAT INTELIJEN KEAMANAN KEPOLISIAN DAERAH SUMATERA BARAT DALAM PENYELIDIKAN PENYALAHGUNAAN SENJATA API ILEGAL OLEH MASYARAKAT - Zamzami Zamzami (UNES Journal of Swara Justisia, 2018)
Article 1 paragraph (1) Emergency Law Number 12 of 1951 describes ownership and use of firearms and sanctions that can be obtained when taking actions that contradict these rules. One of the important roles carried out by the West Sumatra Regional Police Headquarters, destroyed as many as 816 illegal illegal firearms (senpi), the result of Operation Sapu Jagad. This illegal weapon, commonly called Balansa or Gobok, is used by the community to hunt pigs or other disturbing pests. But there are also used by the community for criminal acts that cause victims. This research is an analytical descriptive study, the role of the Directorate of Security Intelligence at the West Sumatra Regional Police in investigating the abuse of illegal weapons in the West Sumatra Regional Police jurisdiction plays a role in repressive actions by conducting a series of preventive investigations and actions, namely conducting patrols and illegal firearms raids , through these actions the Directorate of Security Intelligence throughout 2013 to 2018 received 4 (four) Police Reports related to ownership of firearms by the public. The obstacles faced by the West Sumatra Regional Police Security Intelligence Directorate in investigating illegal weapons abuse, can be seen from internal constraints related to human resources, the budget is still not optimal, inadequate infrastructure and facilities, information coordination, and legislative constraints, while external constraints: lack of community roles, geographical constraints, lack of coordination with local government and nongovernmental organizations. Efforts to overcome these obstacles have been carried out by the Directorate of Security Intelligence by providing training, socializing and cooperating with local governments and non-governmental organizations.